2020
DOI: 10.1093/geroni/igaa025
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Difficulties and Cognition for 10 Years in a National Sample of U.S. Older Adults

Abstract: Background and Objectives Sleep difficulties are common among older adults and are associated with cognitive decline. We used data from a large, nationally representative longitudinal survey of adults over the age of 50 in the U.S. to examine the relationship between specific sleep difficulties and cognitive function over time. Research Design and Methods Longitudinal data from the 2004-2014 waves of the Health and Retirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…1 A growing body of evidence suggests that sleep problems are associated with cognitive impairment and progression to Alzheimer's disease (AD) dementia. 2,3 Sleep disturbances are common in patients with AD dementia; among two-thirds of AD dementia patients report sleep problems, and it is associated with poorer daily functioning. 4 Sleep disturbances have even been suggested as an early symptom of AD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A growing body of evidence suggests that sleep problems are associated with cognitive impairment and progression to Alzheimer's disease (AD) dementia. 2,3 Sleep disturbances are common in patients with AD dementia; among two-thirds of AD dementia patients report sleep problems, and it is associated with poorer daily functioning. 4 Sleep disturbances have even been suggested as an early symptom of AD.…”
Section: Introductionmentioning
confidence: 99%
“…There were differences in total sleep time and sleep efficiency between the any sleep problem (6.7 hours ± 1.2, 83 ± 14%) and no sleep problem group (7.7 hours ± 0.8, 93 ± 7%; all P < .001). There was no difference in time spent in bed (CES-D median [interquartile range (IQR)]: 10[5][6][7][8][9][10][11][12][13][14][15][16] vs. 4[2][3][4][5][6][7]) and anxiety [HADS-A] 5[2][3][4][5][6][7][8][9][10] vs. 2 [0.) than those without sleep problems.…”
mentioning
confidence: 99%
“…Both sleep disturbances and abnormal sleep duration, although both often modifiable, are associated with the development and progression of Alzheimer’s disease [ 2 ]. Furthermore, recent work suggests that older adults (above age 65) who report signs of good sleep health (i.e., reports of waking and feeling refreshed) demonstrate better cognitive function [ 3 ], which may buffer against the development of Alzheimer’s disease and dementia. According to the National Sleep Foundation, there is more sleep disturbance reported among older adults than any other age group [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia symptoms are prevalent nocturnal complaints in older adults that influence different aspects of life. Difficulty falling asleep during the night (initial insomnia type) has been found in older adults to predict depressive cases, 42 persistent severe fatigue, 10 and decreased cognitive function 43 and increased risk for all‐cause mortality after 4–19 years of follow‐up 44 . Related to occupational functioning, our study found that older workers who reported difficulty falling asleep at the beginning of the study were 1.29 times at increased odds to retire from the labor force.…”
Section: Discussionmentioning
confidence: 51%